Limited Utility of Early Life‐History Indices for Predicting Yellow Perch Year‐Class Strength in Eastern South Dakota Glacial Lakes. (24th February 2022) - Dembkowski, Daniel J.; Nelson, Daniel T.; Wuellner, Melissa R.; Blackwell, Brian G.; Lucchesi, David O.; Willis, David W.
Abstract: We used a long‐term data set (2000–2016) of larval, age‐0 (juvenile), and age‐2 Yellow Perch Perca flavescens catches from nine glacial lakes in eastern South Dakota to track multiple cohorts through time to determine whether year‐class strength (measured as gill‐net CPUE of age‐2 fish) could be indexed at the larval or juvenile stage. We observed a strong relationship between larval and juvenile abundance ( r = 0.78), but neither were related to abundance of the same cohort at age 2. Furthermore, categorical analyses suggested that some of the strongest age‐2 year‐classes corresponded with the lowest larval and juvenile catches and vice versa. Our assessment suggests that Yellow Perch year‐class strength in eastern South Dakota glacial lakes may not be fixed until some point after the juvenile (i.e., fall age 0) stage and correspondingly that values for larval and juvenile CPUE are of limited utility as early indices of year‐class strength for Yellow Perch. Before using abundance estimates at early life stages as measures of recruitment, researchers and managers should confirm that these estimates provide a meaningful index of abundance at adulthood or the point of recruitment to the fishery.